The political process evolution in the Volyn region (1991−2021) - Bortnikov, Valerii (Polìtičnì doslìdžennâ, 2022)
A scientific analysis of the political process in the Volyn region for thirty years of existence of independent Ukraine has been carried out in the article. Emphasis has been placed on institutional and non-institutional practices of political activity and participation of subjects of socio-political relations, which determined/determine the nature and direction of the political process in Volyn. The sequence of actions of the government and the opposition to dismantle the institutions of power of the Soviet era, the decommunization of the symbolic space of the settlements of the region, creation of civil society institutions and parties, paradigm shifts in the attitude of local authorities to churches and their denominations, participants in national liberation struggles, etc. have been revealed. Significant influence on the direction of the political process is determined by the electoral participation of citizens in elections to higher and local authorities and, accordingly, qualitative composition of the Verkhovna Rada of Ukraine and local councils. Along with the analysis of the party representation from Volyn in the parliamentary corps of the Ukrainian parliament, there has been traced the dynamics of participation and preferences of certain political forces and parties in the elections to the regional council. The process of party-political structuring in the region has been periodized. The significant attention has been paid to the analysis of socio-political activity of Volyn residents during the Orange Revolution and the Revolution of Dignity. The author came to the conclusion that in general, the political process in Volyn reflects the direction of the political process in Ukraine with its simultaneous diversification in the following main areas: first, the abandonment of authoritarian-totalitarian institutional forms and the transition to democratic ones; secondly, the decommunization of public space and the modeling of historical memory, accompanied by the return of national (local) traditions, rituals and symbols; thirdly, enriching the „paletteˮ of domestic experience in political activities and participation in regional practices.